Empowering practical wisdom from religious traditions: A ricoeurian approach - André Habisch; Claudius Bachmann (International Journal of Corporate Social Responsibility (JCSR), 2016)
Multiple strains of research are currently claiming to bring back normative perspectives into business analysis. In line with a series of publications from different disciplines we refer to the traditional concept of Practical Wisdom for that purpose but link it substantially with narrations from religious and spiritual traditions. Aware of potential resistance against such a project we discuss some basic objections, which might be provoked inside of the business education community. Critics question religious and spiritual traditions as such but also their relevance for modern business practice. Referring to to Paul Ricoeur's concept of metaphorical language we critically sketch a practical wisdom-based approach that employs religious and spiritual traditions as point of reference for responsible management practices but avoids the trap of fundamentalism or normative reductionism. Finally, we will conclude by suggesting the scope of possible applications and the direction of further research.
Keywords: 650; Paul Ricoeur; Practical wisdom; Prudence; Religion; Responsible management; Spiritual traditions; Wisdom